Tahapan Penyusunan Dokumen Rencana Pengamanan Air Minum (RPAM) - Nugraha, Tazkia Safitri; Mohamad Rangga Sururi (Jurnal Serambi Engineering, 2025)
The Drinking Water Safety Plan (WSP) is a systematic approach to ensuring the quality and safety of the community's drinking water. With increasing challenges such as contamination of raw water sources, climate change, and population growth, the development of WSPs is critical to protecting public health from the risks of waterborne diseases. In addition, the lack of guidance in the development of RPAMs indicates that clear documents and training are critical to the successful implementation of WSPs. The process of developing a WSP document involves four main stages: preparation, risk analysis system, management and communication, and feedback. Each stage is designed to help identify and manage risks that may affect the quality of water the community receives. Stakeholder involvement and clear guidance are critical to the successful implementation of the WSP. Through this approach, the WSP is expected to increase community access to safe and quality drinking water in line with the Sustainable Development Goal (SDG) 6.1 target to achieve universal and equitable access to safe and affordable drinking water for all by 2030.